The Effect of Potassium Addition on Oil Palm (Elaeis guineensis Jacq.) Roots Anatomic Properties under Drought Stress - Wiski Irawan; Eka Tarwaca Susila Putra (Caraka Tani: Journal of Sustainable Agriculture, 2020)
The availability of water is one of the main limiting factors for oil palm growth and production. Potassium (K) is an essential nutrient for plants because of its role in controlling metabolic and physiological activities. This study aimed to examine the effect of different K fertilizer doses on root anatomic properties under drought stress. The experiment was arranged in factorial Randomized Complete Block Design (RCBD) with two factors. The first factor was drought stress, consisting of three levels of fractions of transpirable soil water (FTSW) (FTSW 1 (control: field capacity); FTSW 0.35 (moderate drought); FTSW 0.15 (severe drought)) and the second factor was K dose (sourced from KCl), consisting of five levels (K0: 0%; K1: 50%; K2: 100%; K3: 150%; K4: 200%). The results showed that there was an interaction between the addition of K doses and the tolerance level of oil palm plants to drought stress. The addition of 100% K gave higher results in the parameters of xylem diameter, phloem diameter and cortex cell width compared to the plants without K. The results disclosed that 200% K application on moderate drought stress and severe drought stress in oil palm seedlings could widen xylem diameter, phloem diameters, strengthen cell such as epidermal cells, cortex cells, thickness of endodermic cells, thickness of sclerenchyma cells and increase hardness of cell compared to field capacity. As for the parameters of thick endodermic cells, stele diameter and sclerenchyma diameter, an addition of 50% K could give higher results.